Phase-change memory cycling endurance. (September 2019) - Kim, SangBum; Burr, Geoffrey W.; Kim, Wanki; Nam, Sung-Wook
Abstract: Abstract : The cycling endurance of phase-change memory is one of the last hurdles to overcome to enable its adoption in the larger market for persistent memory products. Phase-change memory cycling endurance failures, whether they are stuck-SET (caused by elemental segregation) or stuck-RESET (caused by void formation), are caused by atomic migration. Various driving forces responsible for the atomic migration have been identified, such as hole-wind force, electrostatic force, and crystallization-induced segregation. We introduce several strategies to improve cycling endurance based on an understanding of driving forces and interactions among them. Utilizing some of these endurance-improving techniques, record-high phase-change memory cycling endurance at around 10 12 cycles has been recently reported using a confined phase-change memory cell with a metallic liner.